In-situ gel: a study of dental diseases - Bisht, Neha; Goswami, Laxmi; Kothiyal, Preeti (Creative Pharma Assent, 2014)
In-situ forming polymeric gelling systems has become prominent among novel drug delivery system (NDDS) in recent years due to advantages such as sustained and prolonged drug action, improved patient compliance and reduced frequency of administration of the drug in comparison to conventional drug delivery system (DDS). This is a type of mucoadhesive DDS where the polymeric formulation is in sol form before administration and once comes in contact with body fluids; it undergoes gelation to form a gel. The formulation of gel depends upon factors like temperature modulation, pH changes, presence of ions and ultraviolet irradiation from which drug gets released in sustained and controlled manner. Conventional formulation for the treatment of dental diseases has certain drawbacks. A new concept of in situ gel was develop to overcome the shortcoming of conventional formulation which deals with dental diseases. Conventional oral formulations like solution, suspension, and ointments have many disadvantages which result into poor bioavailability of drug in the buccal cavity. In-situ forming polymeric formulation drug delivery systems is in sol form before administration in the body, but once administered, undergoes gelation in-situ to form a gel.